Spatial orientations and structural irregularities associated with the formation of microbands in a cold deformed Goss oriented Ni single crystal - Afrin, N.; Quadir, Md Zakaria; Xu, W.; Ferry, M. (Pergamon Press, 2012)
The crystallographic nature of microband boundaries was investigated in a Goss oriented nickel single crystal following cold deformation in channel die plane strain compression. Standard electron backscatter diffraction (EBSD), three-dimensional (3-D)-EBSD and transmission electron microscopy (TEM) were used in the investigation. When viewed in the three orthogonal sections microband boundary traces were classically aligned in the transverse direction section at an acute angle from the rolling direction (RD), but appeared wavy in the normal direction (ND) section. The latter observation may lead to the conclusion that microband boundaries are non-crystallographic. 3-D EBSD was used to reconstruct actual microbands in a deformed volume that revealed significant new information about their structure. Here microband surfaces are largely planar over large distances, but frequently interrupted by local distortions and undulations due to interactions between intersecting non-coplanar microbands. The combined EBSD/TEM investigation has revealed that microband boundaries are aligned close to an active {1 1 1} slip plane (i.e. they are crystallographic), but the undulations and distortions they contain are non-crystallographic in the sense that they deviate from an active slip plane. The non-crystallographic features of microbands (as revealed by their wavy structure in the ND section) may be explained by the crystallographic oscillations of up to ±7.5° towards RD that occur during plastic deformation. Such oscillations result in varying fractions of slip on a given {1 1 1} plane, resulting in varying degrees of interaction between the two sets of non-coplanar microbands. These local and intense microband interactions result in their deviation from their active slip planes.